Peran Badan Amil Baitul Mal Dalam Menghimpun Zakat Profesi PNS Di Kabupaten Aceh Tamiang - Fachrurrazy, Muhammad; Ulfa, Maria (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2023)
Purpose – This research was conducted to determine the level of suitability and implementation of the collection of professional zakat funds for Civil Servants (ASN) in increasing muzzaki awareness. Method – This research uses a descriptive method with a qualitative approach with primary and secondary data. Data collection methods used were observation, interviews and documentation. The informants for this research were two people from Baitul Mal Aceh Tamiang and the BPKD, while the respondents were three people who had the status of muzakki at Baitul Mal Aceh Tamiang. Results – The results of the research show that the collection of professional zakat funds has not been fully effective because funds are collected through 2 ASN criteria, namely Active ASN and Passive ASN, there are still obstacles in Passive ASN which are still less aware of paying zakat, thus having a big impact in increasing awareness of muzakki paying zakat profession. Practical Implication – As a practical implication, the results of this research can be used as a reference to better understand the attitudes and regulations that must be taken to create new policies.